Program penggemukan ternak sapi potong dan pembentukan kelompok ternak armadadi Kawasan Ekonomi Khusus Mandalika Kabupaten Lombok Tengah Nusa Tenggara Barat: Beef Cattle Fattening Program and Establishment of Fleet Cattle Groups in Mandalika Special Economic Zone, Lombok Tengah Regency Nusa Tenggara Barat - Yuliani, M. Gandul Atik; Ma'ruf, Anwar; Yuliawan, Rahmat; Rochmi, Siti Eliana (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT The Mandalika Special Economic Zone, located in Central Lombok district, West Nusa Tenggara province, is expected to accelerate the tourism sector on the island of Lombok. The Mandalika KEK has potential and advantages that can be developed into an environmentally friendly tourism area. Tourist objects and tourist attractions are expected to always be oriented towards preserving environmental values ​​and quality in society. This increase in the tourism sector will be followed by an increase in the food sector and beef cattle farming is one of them. This Community Service Activity was carried out on Sunday 13 August 2023 at the Reading Corner room managed by Karang Taruna, Pujut District, Central Lombok Regency, West Nusa Tenggara Regency. Approximately 50 breeders around the location attended. This meeting also formed a Breeders Community called